Inflammatory responses in oro-maxillofacial gegion expanded using anisotropic hydrogel tissue expander - Ali Salim, KM; Abd Jalil, A; Radzi, Z; Ismail, SM; Czernuszka, JT; Rahman, MT (MDPI, 2020)
Objective: Reconstruction of oral and facial defects often necessitate replacement of missing soft tissue. The purpose of tissue expanders is to grow healthy supplementary tissue under a controlled force. This study investigates the inflammatory responses associated with the force generated from the use of anisotropic hydrogel tissue expanders. Methods: Sprague Dawley rats (n = 7, body weight = 300 g ± 50 g) were grouped randomly into two groups—control (n = 3) and expanded (n = 4). Anisotropic hydrogel tissue expanders were inserted into the frontal maxillofacial region of the rats in the expanded group. The rats were sacrificed, and skin samples were harvested, fixed in formalin, and embedded in paraffin wax for histological investigation. Hematoxylin and eosin staining was performed to detect histological changes between the two groups and to investigate the inflammatory response in the expanded samples. Three inflammatory markers, namely interleukin (IL)-1α, IL-6, and tumor necrosis factor-α (TNF-α), were analyzed by immunohistochemistry. Result: IL-1-α expression was only observed in the expanded tissue samples compared to the controls. In contrast, there was no significant difference in IL-6, and TNF-α production. Histological analysis showed the absence of inflammatory response in expanded tissues, and a negative non-significant correlation (Spearman’s correlation coefficient) between IL-1-α immune-positive cells and the inflammatory cells (r = −0.500). In conclusion, tissues that are expanded and stabilized using an anisotropic self-inflating hydrogel tissue expander might be useful for tissue replacement and engraftment as the expanded tissue does not show any sign of inflammatory responses. Detection of IL-1-α in the expanded tissues warrants further investigation for its involvement without any visible inflammatory response.